2010
DOI: 10.2134/agronj2009.0398
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Water Use and Lint Yield in Four Great Plains Soils

Abstract: The development of earlier maturing, cool temperature tolerant varieties of cotton (Gossypium hirsutum L.) has allowed cotton production to expand into regions with shorter, cooler growing seasons. The objective of this research was to evaluate the interactive effect of soil type, irrigation, and meteorological conditions on the water use and lint yield of cotton grown in four U.S. Great Plains soils. Cotton was grown in 2005 through 2007 in 48 weighing lysimeters which contained clay loam, silt loam, sandy lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Pearson correlations (Table 4) also revealed that lint yield increased with increasing boll number ( r = 0.41) as similarly observed by Tolk and Howell (2010). The number of bolls plant −1 , however, decreased with increasing plant population ( r = −0.21), but not enough to depress the lint yield.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Pearson correlations (Table 4) also revealed that lint yield increased with increasing boll number ( r = 0.41) as similarly observed by Tolk and Howell (2010). The number of bolls plant −1 , however, decreased with increasing plant population ( r = −0.21), but not enough to depress the lint yield.…”
Section: Resultssupporting
confidence: 69%
“…A similar net demand of 400 to 600 mm irrigation to supplement the 28‐yr mean seasonal precipitation of 384 mm for a total water use at Bushland of ∼800 to 1000 mm (Howell et al, 1989) led to a recommended minimum net irrigation capacity of 8 mm d −1 for sprinkler irrigated corn. For cotton, the 3 yr growing season water use averaged ∼640 mm for a slightly smaller ∼7.1 mm d −1 net irrigation capacity that replaced 100% of the adjusted ET and produced ∼500 kg ha −1 mean lint yield increase over the 50% irrigation treatment yield of ∼1000 kg ha −1 lint (Tolk and Howell, 2010). Similarly, Baumhardt et al (2009) modeled cotton lint yields of 600 to 700 kg ha −1 with seasonal net water use of 550 to 600 mm for irrigation capacities of 2.5 to 5.0 mm d −1 that were applied to soil having low initial water content.…”
mentioning
confidence: 99%
“…However, under current SHP climate conditions, there is less than a 5% probability that 15 May-15 October GDD totals would exceed 1400.0 • C [2]. The SHP summer environment has been generally noted to be cool and degree-day limited relative to the requirements of cotton crop development [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, it may increase with depth when coal occurs in lower horizons (Ibrahim et al, 2011), or the soil is a Histosol (Hussein et al, 2004;Ibrahim and Lal, 2014). The concentration of SIC may either increase (Khan and Fenton, 1994;Onweremadu, 2007), or decrease with depth (Tolk and Howell, 2010).…”
Section: Peer Reviewed Papersmentioning
confidence: 99%